PERBEDAAN PENERIMAAN DIRI ORANG TUA YANG MEMILIKI ABK BERDASARKAN KEIKUTSERTAAN DALAM KEGIATAN SUPPORT GROUP - Iriani Indri Hapsari; Herdiyan Maulana (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
The aim of this research was to analyse the differences between the self acceptence of parents with handicapped children based on their involvment in the support group compared to those without any involvement. In this research, 64 parents with handicapped children were selected using nonprobability sampling with incidental sampling type. The samples comprised of 32 parents with involvement in support group and the remaining were without any involvement. Adapted Berger Self Acceptance Scale was used for the measurement of the research. Independent sample T-Test was the statistical analysis method used for the research. The result showed that t = 0, 267 with df = 62 ; t < t able (2) and p = 0,79 ; p > 0,05, meaning Ho was accepted and H1 was rejected. The result showed that there is no significance different between self acceptence of parents with handicaped children who join the support group with those who have not joined the group. Discussion of this research concluded there are several factors influencing this finding, such as family, cultural problems, and religious view, beside social and economic status.